Fractionation of graphene oxide single nano-sheets in water-glycerol solutions using gradient centrifugation. (July 2016) - Bidram, Elham; Sulistio, Adrian; Amini, Abbas; Fu, Qiang; Qiao, Greg G.; Stewart, Alastair; Dunstan, Dave E.
Abstract: A centrifugation method for the separation and fractionation of graphene oxide (GO) single nano-sheets in the size range of 150–850 nm is reported. The measured electrophoretic mobility of the fractionated single sheets ranges from −0.2 to −1.4 μm cm/V·s where the interpreted zeta potentials vary from −3 mV to −17 mV with increasing sheet size. The single GO sheets show auto-fluorescence in the visible range of 350–650 nm using an excitation wavelength of 200 nm. Furthermore, the GO nano-sheets functionalized using PEG are found to be non-cytotoxic in in-vitro at concentrations up to 90 μg/ml, with a small reduction in cell viability −10%- at 260 μg/ml. The observed concentration-dependence of the cytotoxicity potentially explains the differing conclusions on cytotoxic potential reported in the literature. The GO nano-sheets therefore have the potential to be used as fluorescent drug delivery carriers of specific size.